2019
DOI: 10.1038/s41467-019-08773-2
|View full text |Cite
|
Sign up to set email alerts
|

A MST1–FOXO1 cascade establishes endothelial tip cell polarity and facilitates sprouting angiogenesis

Abstract: Hypoxia is a main driver of sprouting angiogenesis, but how tip endothelial cells are directed to hypoxic regions remains poorly understood. Here, we show that an endothelial MST1–FOXO1 cascade is essential for directional migration of tip cells towards hypoxic regions. In mice, endothelial‐specific deletion of either MST1 or FOXO1 leads to the loss of tip cell polarity and subsequent impairment of sprouting angiogenesis. Mechanistically, MST1 is activated by reactive oxygen species (ROS) produced in mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 65 publications
4
60
0
Order By: Relevance
“…In particular, recent evidence suggests that hypoxiainduced reactive oxygen species (ROS) biosynthesis from mitochondria could be a major upstream regulator of Stk4 activation in endothelial cells. Activated stk4 promotes planar and perpendicular vascular branching for regulating tip endothelial cells polarity and sprouting angiogenesis (Kim et al, 2019). Moreover, it was recently shown that STK4 acts as pro-apoptotic factor in damaged venous endothelial cells by the MIEF1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent evidence suggests that hypoxiainduced reactive oxygen species (ROS) biosynthesis from mitochondria could be a major upstream regulator of Stk4 activation in endothelial cells. Activated stk4 promotes planar and perpendicular vascular branching for regulating tip endothelial cells polarity and sprouting angiogenesis (Kim et al, 2019). Moreover, it was recently shown that STK4 acts as pro-apoptotic factor in damaged venous endothelial cells by the MIEF1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The knock-down of Nucleolin in HUVECs lead to disorientation of the actin cytoskeleton inducing a loss of cell polarization as indicated by a change in cell shape towards a less elongated phenotype. Recent evidence suggests that MST1–FOXO1-mediated endothelial tip cell polarity facilitates sprouting angiogenesis 95 . MST1-FOXO1 was shown to be essential for directional migration of tip cells towards hypoxic regions and endothelial-specific deletion of either MST1 or FOXO1 lead to loss of endothelial tip cell polarity resulting in impaired sprouting angiogenesis 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that MST1–FOXO1-mediated endothelial tip cell polarity facilitates sprouting angiogenesis 95 . MST1-FOXO1 was shown to be essential for directional migration of tip cells towards hypoxic regions and endothelial-specific deletion of either MST1 or FOXO1 lead to loss of endothelial tip cell polarity resulting in impaired sprouting angiogenesis 95 . Indeed, in our bulk RNA sequencing data, we found a downregulation of FOXO1 upon Nucleolin knock-down, indicating a regulatory role for Nucleolin on MST1-FOXO1-mediated regulation of cell polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear FOXO1 will, in turn, activate the transcription of genes involved in the regulation of cell polarity and directional migration of tip cells toward hypoxic regions (Fig. 1) (94). Curiously, FOXO1 has been previously associated with the regulation of EC metabolism and quiescence (95).…”
Section: Dynamics Of Blood Vessel Formationmentioning
confidence: 99%